Professional Public Relations (PR) trends and challenges. - Almansa-Martínez, Ana María; Fernández Souto, Ana Belén (Profesionales de la Información, 2020)
There are several studies and reports that identify the challenges that Public Relations must assume in the coming years, but how will the professional field face them? Are the organizations and institutions prepared to assume the new needs that constant adaptation demands? What are the priorities that they must establish so that the profession is renewed? The profession, in order to face the challenges that the future holds in the changing society in which we live, must commit itself to training. Thanks to training, public relations professionals will be able to achieve a high degree of specialization in the discipline. Strategic vision, Public Relations (PR) assessment, commitment to quality and professional ethics, transparency, as well as inclusion and equality must be the benchmarks of the sector.
Keywords: Relaciones públicas; Public Relations; PR; Challenges; Trends; Training; Professional career; Research